Complete genome sequence of Methanoculleus marisnigri Romesser et al. 1981 type strain JR1. Issue 2 (September 2009) - Anderson, Iain; Sieprawska-Lupa, Magdalena; Lapidus, Alla; Nolan, Matt; Copeland, Alex; Glavina Del Rio, Tijana; Tice, Hope; Dalin, Eileen; Barry, Kerrie; Saunders, Elizabeth; Han, Cliff; Brettin, Thomas; et al.
Abstract Methanoculleus marisnigri Romesser et al. 1981 is a methanogen belonging to the orderMethanomicrobiales within the archaeal phylumEuryarchaeota . The type strain, JR1, was isolated from anoxic sediments of the Black Sea.M. marisnigri is of phylogenetic interest because at the time the sequencing project began only one genome had previously been sequenced from the orderMethanomicrobiales . We report here the complete genome sequence ofM. marisnigri type strain JR1 and its annotation. This is part of a Joint Genome Institute 2006 Community Sequencing Program to sequence genomes of diverseArchaea .